363 MANAGEMENT OF COMPLEX ADVERSE EVENTS AFTER PARAESOPHAGEAL HERNIA REPAIR: EXPERIENCE OF A HIGH-VOLUME REFERRAL CENTRE. (14th September 2020) - Antoun, A; Karam, A; Trépanier, M; Cools-Lartigue, J; Ferri, L; Mueller, C
Abstract:  : Adverse events after paraesophageal hernia repair (PEHR), including persistent dysphagia, acute and delayed recurrence, and gastroesophageal perforation, can present complex management challenges. Medical, endoscopic and surgical treatments may be used, but descriptions of when to employ these options and how to choose a surgical approach (e.g. open vs laparoscopic, transabdominal vs transthoracic), are limited. We sought to review the treatment and outcome for complex adverse events after PEHR. Methods: All patients undergoing primary (elective or emergency) and revisional repair of PEH at a high volume specialized referral center were identified. Demographic data, operative details and outcomes were verified by chart review. Extracted data included patient characteristics, incidence of adverse events, and diagnostic and management strategies. Details of endoscopic and surgical interventions for complex recurrences were tabulated. Results: 369 patients with PEHR were identified from 2012-19. Most (345:94%) underwent the index PEHR at our centre, with 24(6%) referred from other institutions for management of adverse events. Post-operative dysphagia requiring invasive intervention occurred in 27(7.3%), and 23(6.2%) required re-operation (19 laparoscopically). Gastric or esophageal perforations diagnosed post-operatively occurred in 11(3.0%), of which 8(72.7%) required emergency reoperation (1 laparoscopic, 2 laparotomy, 2 thoracotomy and 3 by combined abdominal/thoracic approach). Of 69 recurrences, 11 presented with incarceration requiring emergency surgery (8 repaired laparoscopically, 2 converted to laparotomy, and 2 required combined laparotomy/thoracotomy). One perioperative death occurred in this series. Conclusion: Complex adverse events after PEH repair comprise a unique challenge given the wide variety of management options. When faced with these challenges, one should consider utilizing a customized surgical approach that varies with patient condition, anatomical characteristics of the complication and surgeon preference.